Portrayal of Bullying in Selected Picture Books: A Content Analysis - William Bintz (Athens Journal of Education, 2023)
This article discusses findings and implications from a research study using content analysis to investigate one question: How is bullying portrayed in selected picture books? The question is important because bullying has been, and continues to be, a pervasive problem in and out of school. This research study is needed because it investigates portrayals of the bully, bullied, and bystanders, unlike previous research that focused only on the bully. This article provides a review of research on bullying, highlighting international and national research that used content analysis to analyze picture books on bullying. It discusses content analysis as the research methodology, and describes data sources, data categories, data collection methods, and data analysis procedures. It ends by identifying major findings, discussing implications of findings, and describing limitations of the study.